Negotiating identity : Nakagami Kenji's Kiseki and the power of the tale - Thelle, Anne Helene (Iaponia insula, 2010)
Nakagami Kenji is today regarded as one of the most important and influential Japanese post-war writers. Born in 1946 in the burakumin ghetto of the small coastal town of Shingu in southern Wakayama prefecture, Nakagami sailed up as a rising star on the literary skies in the mid-seventies when he became the first writer born after the Second World War to win the prestigious Akutagawa prize. He was also the first writer of the burakumin background to receive wide literary acclaim and recognition from critics and from the literary establishment. The reception of Nakagami's literature.